PENGARUH PERAN KEPALA SEKOLAH DAN KOMITE SEKOLAH TERHADAP MUTU PENDIDIKAN PADA SMP NEGERI DI KABUPATEN ROKAN HILIR - Suwanto Suwanto; Makhdalena Makhdalena; Azhar Azhar (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2019)
This study aims to determine the headmaster’s participation and school committee participation towards eduaction quality on public junior high schools (SMPNs) in Rokan Hilir district. The research was conducted at the Junior High School in Rokan Hilir. the study was conducted over three months, from September 2015 to November 2015. The results show that there is a positive relationship between headmaster’s participation and quality of education. Partially, the headmaster’s participation affects 90.0% of the value quality of education at Junior High School in Rokan Hilir, meaning the better headmaster’s participation will increase the quality of education. There is a positive relationship between school committee participation with the quality of education. Partially, school committee participation affects 58.3% of the value of the quality of education at the Junior High School in Rokan Hilir, meaning the better school committee participation will increase the quality of education. There is a positive relationship between the headmaster’s participation and school committee participation together with the quality of education. Headmaster’s participation and t school committee participation jointly affect the 90.4% value of the quality of education at the Junior High School in Rokan Hilir.